2017
DOI: 10.1007/s00402-017-2788-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes of femoral offset on abductor and joint reaction forces in total hip arthroplasty

Abstract: To our knowledge, this is the first report providing quantitative data on the effect of FO changes on muscle and joint forces during normal gait. A decrease of FO necessitates an increase of abductor muscle force to maintain normal gait, which in turn increases the joint reaction force. This effect underscores the importance of an accurate reconstruction of the femoral offset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 31 publications
2
42
1
3
Order By: Relevance
“…Accurate surgical techniques as well as optimal prosthesis design and positioning, can reduce the impact of joint replacement on peripheral muscle function. A previous study suggested that accurate intraoperative femoral offset reconstruction is essential for maintaining the abductor muscle moment arm [8]. The displacement of the centre of the femoral head may occur due to surgeon preferences (e.g., excessive correction of native femoral anteversion), inaccurate preoperative templating, or limited selection of available implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate surgical techniques as well as optimal prosthesis design and positioning, can reduce the impact of joint replacement on peripheral muscle function. A previous study suggested that accurate intraoperative femoral offset reconstruction is essential for maintaining the abductor muscle moment arm [8]. The displacement of the centre of the femoral head may occur due to surgeon preferences (e.g., excessive correction of native femoral anteversion), inaccurate preoperative templating, or limited selection of available implants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have demonstrated that insu cient muscle strength and tension in the hip abductor and adductor muscles (nerve injury or limb shortening) are the causes of THA dislocation [6,7]. Rudiger et al [8] reported that the decrease in the femoral offset after THA would reduce the abductor moment arms during gait using musculoskeletal model in OpenSim. Precise evaluation of the function of the hip abductor and adductor muscles in THA patients during gait could help prevent postoperative complications and optimize the rehabilitation training program.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that most of the comparative studies have focused on cup position but have largely ignored the femoral component with the exception of leg length. Femoral offset and/or total offset can substantially affect the function of the hip abductor muscles [12,13]. During hip replacement, most surgeons attempt to position the acetabular component in a relative "safe zone" and utilize the femoral component to recreate leg length and offset.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative changes in femoral offset may lead to altered muscular function that can result in hip abductor muscle insu ciency and pain as well as early prosthesis wear [2,3]. Furthermore, loss of femoral offset necessitates increased abductor muscle force to maintain normal gait pattern [4], and a loss exceeding 15% can result in gait alterations [5].…”
Section: Introductionmentioning
confidence: 99%